2006
DOI: 10.1002/rcm.2467
|View full text |Cite
|
Sign up to set email alerts
|

A high‐performance liquid chromatography/tandem mass spectrometry method for the determination of artemisinin in rat plasma

Abstract: Artemisinin is a widely used antimalarial drug. To evaluate the pharmacokinetics of artemisinin in rats, a sensitive and specific liquid chromatography/tandem mass spectrometric (LC/MS/MS) method was developed and validated for the determination of artemisinin in rat plasma. For detection, a Sciex API 4000 LC/MS/MS instrument with an electrospray ionization (ESI) TurboIonSpray inlet in the positive ion multiple reaction monitoring (MRM) mode was used to monitor precursor ([M+NH4]+) --> product ions of m/z 300.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 15 publications
0
34
0
1
Order By: Relevance
“…Artemether Previous reports on the MS detection of the artemether molecule 18,19 have reported on the failure to observe the intact protonated molecule and used therefore only fragments and secondary dissociations for its quantitation. of a neutral LiOCH 3 forms the product ion of m/z 221, which dissociates in turn by the loss of acetone to form the ion of m/z 163.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Artemether Previous reports on the MS detection of the artemether molecule 18,19 have reported on the failure to observe the intact protonated molecule and used therefore only fragments and secondary dissociations for its quantitation. of a neutral LiOCH 3 forms the product ion of m/z 221, which dissociates in turn by the loss of acetone to form the ion of m/z 163.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports on the MS detection of the artemether molecule 18,19 have reported on the failure to observe the intact protonated molecule and used therefore only fragments and secondary dissociations for its quantitation. 18 and Xing et al 19 also found an ion of m/z 163 for the ESI-MS of artemether and proposed a distinct chemical structure for it based on a different mechanistic rationalization.…”
Section: Artemethermentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19][20] Currently, the suitable method for quantification of these compounds in plasma is liquid chromatography coupled with mass spectrometry detection (LC-Ms or LC-MS/MS) with quantification limits of approximately 1 ng/mL using only 50-μL plasma sample volumes. [21][22][23][24][25] However, some of the problems encountered the latter bioanalytical methods include lack of appropriate stable isotope-labeled AS and DHA internal standards, in addition to expensive solid phase extraction cartridges that most commonly used for extraction of AS and DHA from biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…Some other recent methods for the assay of these drugs alone or in combination with other antimalarials have also been reported [24][25][26][27][28]. However, these methods still had some limitations related to the chromatography and detection in terms of resolution, time-consuming, and requiring prolonged derivatization.…”
Section: Introductionmentioning
confidence: 99%